Utilization of Complementary and Alternative Medicine among Patients with Cardiovascular Disease in Iran: A Cross-Sectional Study - Mohammad Hossein Sharifi; Salman Mohammadi; Naseh Pahlavani; Ali Ghaffarian-Bahraman; Sara Darabi; Mohammad Hossein Nikoo; Mohammad Ebrahim Zohalinezhad (Tehran University of Medical Sciences, 2024)
Complementary Alternative Medicine (CAM) has been widely used globally, but limited data are available on the use of CAM in Cardiovascular Disease (CVD). The present study aimed to evaluate CAM use in CVD patients. The present cross-sectional study was performed in Shiraz, Iran, during the summer of 2021. Cardiovascular patients aged ≥ 18 years were included in the study. Demographic information on left ventricular ejection fraction and satisfaction with CAM utilization was collected using validated questionnaires. A total of 304 patients (194 males and 110 females) were recruited for this study. The frequency of patients identified as CAM users was 56.9% (n = 173). Patients with implanted pacemakers were less likely to use CAM than others (OR = 0.50, p = 0.031). Meanwhile, the likelihood of CAM utilization was approximately 2 and 4 times higher in the patients categorized in class I of the New York Heart Association (NYHA) functional classification compared to those in the second and third classes, respectively. Most CAM users used herbs, dietary supplements, and praying to prevent diseases, while Traditional Persian Medicine (TPM) remedies and acupuncture were more commonly used to treat acute and chronic illnesses, respectively. Praying for health, herbal therapy, and dietary supplementation were the most popular CAM types utilized by Iranian CVD patients. However, future investigations seem to be required to determine the exact physiological impacts, probable adverse effects, and long-term benefits of CAM therapies in this population.